Projective processes and neuroscience in art and design - Zuanon, Rachel (A volume in the advances in media, entertainment, and the arts (AMEA) book series, 2017)
This book provides a forum for discussion relating to the intersection of projective processes and cognitive neuroscience, offering a neuroscientific perspective on the roles and responsibilities of designers and artists, with relation to the products they design.